Data Survey of Seismically Isolated Buildings in the Expected Tsunami Inundation Areas in Japan - Masahito Kobayashi; Norifumi Hirata (Engineering Reports)
ABSTRACT Tsunamis strike frequently around the world, causing enormous damage. Examples include the 2004 Indian Ocean earthquake and tsunami and the 2011 earthquake off the Pacific Coast of Tohoku. Japan is one of the countries most affected by tsunamis. Detailed data about the number of buildings in the expected tsunami inundation areas in Japan—including by use and inundation depth—are therefore useful in planning buildings not only in Japan, but also in other countries where tsunami damage is expected. Among more than 5000 seismically isolated buildings (SIBs) that have been constructed in Japan, however, only a very few were designed with tsunami countermeasures. In some SIBs, tsunamis have even inundated the seismic isolation device. The relationship between the locations planned for future SIBs and the expected tsunami inundation areas is therefore very important. In this work, we have surveyed approximately 1600 SIBs based on design data provided by performance‐evaluation organizations and have used the data published by each prefecture to prepare tsunami inundation maps. Our survey results show that Kanagawa and Osaka have large percentages of SIBs constructed in the expected tsunami inundation areas. In addition, the largest percentage of all the SIBs in the expected tsunami inundation areas—40%—has been built in areas where the inundation depth is expected to be 1–3 m. Even buildings like hospitals and government buildings, which must maintain their functions during disasters, have been constructed in areas where the expected inundation depth is 5–10 m.